Analysis of 24Slot wound field salient rotor switched-flux machine based on 2D-FEA. (3rd October 2016) - Khan, Faisal; Sulaiman, Erwan; Ali Soomro, Hassan; Omar, Fairoz; Ahmad, Zarafi
Abstract : Purpose: The paper aims to propose and compare two new structures of a three-phase wound field salient rotor (WFSR) switched-flux motor (SFM) with 24 stator slots and 10 or 14 rotor poles, respectively, for high-speed operation. Design/methodology/approach: The paper outlines the motor general construction and design concept of proposed machines. Flux linkage, average torque, rotor mechanical strength and torque–speed characteristics of both machines were analyzed and compared by two-dimensional finite element analysis (2D-FEA). Deterministic optimization method was adopted to enhance the characteristics of 24Slot-10Pole WFSR SFM. Findings: The paper provides simulation results and discusses how 24Slot-10Pole WFSR SFM structure is superior to the 24Slot-14Pole in the aspects of flux linkage, average torque and power. It further concludes that the optimized design of 24Slot-10P has achieved 58 and 72 per cent higher average torque and power compared to initial design, as well as high average torque and power compared to 24Slot-14P design. Originality value: Optimized structure of the 24Slot-10Pole WFSR SFM with non-overlapping windings has been proposed.